A mini review on the short-type peptidoglycan recognition protein in Chinese soft-shelled turtle (Pelodiscus sinensis). Issue 1 (November 2021) - Huang, L; Yu, Q; Liu, M Z; Liao, J Q; Li, P F
Abstract: Peptidoglycan recognition proteins (PGRPs) function as the pattern recognition receptor involved in antibacterial innate immunity. Evidence have showed that the molecular structure and function of PGRPs was conserved in vertebrate. However, as the pivotal species in the evolution of vertebrates, reptiles are believed to be the first vertebrates that have escaped from the aquatic environment and are able to adapt to a variety of different terrestrial lives, few studies about the PGRPs in reptiles has been reported. The Chinese soft-shelled turtle, Pelodiscus sinensis, is an ancient, secondary aquatic reptile with high economic value and nutritional value in Asia, which occupies a unique position in the animal kingdom and has important research value. In the latest research, a PGRP gene which was classified into the member of short-type PGRP family was characterized in Pelodiscus sinensis . This paper presented the latest findings on the molecular structure, expression pattern and function feature of PGRP-S from Pelodiscus sinensis, aiming at revealing that PGRP in vertebrates is evolutionarily conserved.